Synthesis and Spectroscopic Studies of Metal Complexes of Schiff Base Derived from 2-Phenyl-3-(p-aminophenyl)-4-quinozolone - Rai, B.K.; Vidyarathi, S.N.; Kumari, Punam; Kumari, Suman; Lakshmi, Kumari; Singh, Rajkishore (Asian Journal of Chemistry, 2012)
Ten coordination compounds of Co(II), Ni(II) and Cu(II) with Schiff base ligand 2-phenyl-3-(p-aminophenyl)-4-quinazolone hydrazone (PAQH) were synthesized and characterized by molar mass elemental analyses, magnetic susceptibility, infrared spectra, electronic spectra and molar conductance measurements. All the synthesized compounds were screened for antimicrobial activities against two bacteria, Escherichia coli and Staphylococcus aureus. Metal complexes exhibit several fold increase in their antimicrobial activity in comparison to that of the constituting ligand fragments. The complexes of Co(II) and Ni(II) were proposed to be octahedral in geometry whereas the geometry of Cu(II) complexes were proposed distorted octahedral.